Predicting the popularity of tweets using the theory of point processes. - Tan, Wai Hong (2019)
This thesis focuses on the problem of predicting the tweet popularity, or the number of retweets stemming from an original tweet. We propose several prediction methodologies using the theory of point processes, where the prediction of the future popularity of a tweet is based on observing the retweet time sequence up to a certain censoring time, and the prediction performance is evaluated on a large Twitter data set.